Analisis Kualitas Air Limbah Domestik Berdasarkan Parameter pH, Amonia, dan Chemical Oxygen Demand (COD) untuk Evaluasi Lingkungan - Nurul Hafifah; Jon Efendi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the quality of domestic wastewater based on three main parameters: pH, ammonia, and Chemical Oxygen Demand (COD). The wastewater samples were collected from an industrial area, chosen for its role as a primary source of domestic waste that can impact environmental quality. The pH was tested using potentiometry, while ammonia and COD concentrations were measured using UV-Vis spectrophotometry, a precise method for analyzing these substances. The results showed that the pH values of the wastewater ranged from 6.68 to 10.28. This variation in pH reflects the acidity or alkalinity of the wastewater, with some samples being neutral to slightly alkaline. The ammonia levels detected ranged from 0.0654 to 0.3849 mg/L. While these levels are within the limits set by regulations, they indicate a significant presence of ammonia in the wastewater, which requires continued monitoring. However, the most striking finding was the COD levels, which ranged from 21.60 to 245.71 mg/L, with some samples showing very high values. High COD levels indicate a large presence of organic matter, which can lead to a decline in water quality. Some samples with COD values exceeding the threshold of domestic wastewater quality standards, as stated in Ministerial Regulation No. 68 of 2016, require additional treatment to reduce organic contamination. Overall, while the pH and ammonia values remain within safe limits, the high COD levels in some samples indicate that further treatment is necessary to reduce organic pollution. This study emphasizes the importance of routine monitoring of domestic wastewater to protect environmental quality and prevent broader negative impacts on aquatic ecosystems and human health.